A Structural Model of Adolescents’ Externalizing Behaviors Based on Early Maladaptive Schemas, Alexithymia, and Reward Sensitivity: The Mediating Role of Self-Control and the Moderating Role of Autonomous Motivation - Navidi Moghadam, Masoud (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to develop and test a structural model of adolescents’ externalizing behaviors based on early maladaptive schemas, alexithymia, and reward sensitivity, with the mediating role of self-control and the moderating role of autonomous motivation. Methods and Materials: This descriptive-correlational study employed structural equation modeling to examine the proposed relationships among the study variables. The statistical population consisted of high school students in Tehran during the 2025–2026 academic year. Using a multistage cluster sampling method, 620 adolescents were selected and completed the Youth Self-Report Externalizing Problems Scale, Young Schema Questionnaire–Short Form, Toronto Alexithymia Scale, Sensitivity to Reward Questionnaire, Self-Control Scale, and Autonomous Motivation Scale. Data were analyzed using SPSS-27 and AMOS-26 through descriptive statistics, Pearson correlation analysis, confirmatory factor analysis, structural equation modeling, bootstrapping procedures, and latent interaction analysis. Findings: The results indicated that early maladaptive schemas, alexithymia, and reward sensitivity had significant positive direct effects on externalizing behaviors. Furthermore, all three predictor variables demonstrated significant negative effects on self-control, whereas self-control exhibited a significant negative effect on externalizing behaviors. Bootstrapping analyses confirmed the mediating role of self-control in the relationships between early maladaptive schemas and externalizing behaviors, alexithymia and externalizing behaviors, and reward sensitivity and externalizing behaviors. The interaction analysis revealed a significant moderating effect of autonomous motivation on the relationship between self-control and externalizing behaviors, indicating that the protective influence of self-control was stronger among adolescents with higher levels of autonomous motivation. The final structural model demonstrated satisfactory fit indices and explained 58% of the variance in self-control and 67% of the variance in externalizing behaviors. Conclusion: The findings support an integrative developmental model suggesting that adolescents’ externalizing behaviors are influenced by cognitive vulnerabilities, emotional processing deficits, and motivational tendencies both directly and indirectly through self-regulatory mechanisms. Self-control serves as a key explanatory pathway linking maladaptive schemas, alexithymia, and reward sensitivity to behavioral problems, while autonomous motivation strengthens the protective effects of self-regulation. Interventions aimed at enhancing self-control, emotional awareness, adaptive schema functioning, and autonomous motivation may be effective in preventing and reducing externalizing behaviors among adolescents.